2018
DOI: 10.3390/en11123462
|View full text |Cite
|
Sign up to set email alerts
|

Financial Market Development and Pollution Nexus in Saudi Arabia: Asymmetrical Analysis

Abstract: The study is aimed to scrutinize the presence of Environmental Kuznets Curve (EKC) hypothesis in Saudi Arabia by analyzing a period of 1971-2014. Asymmetrical impacts of Financial Market Development (FMD) and energy consumption per capita have also been tested on CO 2 emissions per capita. The estimates buoyed the long and short-run relationships in the hypothesized model, and EKC is found to be true in terms of the relationship between income and pollution. Asymmetrical effects of FMD in the long run and asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
(80 reference statements)
2
22
0
Order By: Relevance
“…Mahmood et al [32] and Shahbaz et al [33] have investigated and corroborated the asymmetrical effects of financial development on CO 2 emissions in the case of Saudi Arabia and Pakistan, respectively. Siddiqui et al [34] found the asymmetrical effects of oil price on the stock markets in some Asian countries.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Mahmood et al [32] and Shahbaz et al [33] have investigated and corroborated the asymmetrical effects of financial development on CO 2 emissions in the case of Saudi Arabia and Pakistan, respectively. Siddiqui et al [34] found the asymmetrical effects of oil price on the stock markets in some Asian countries.…”
Section: Literature Reviewmentioning
confidence: 89%
“…In conclusion, both positive or negative effect may be expected on the theoretical predictions and exact relationship should confirm from rigorous empirical exercise. For this purpose, we hypothesize the following model: Assuming symmetry in the relationships may be accounted for specification biasness in the presence of statistically significant asymmetry [10][11][12]. Considering this fact, we may split each independent variable into two variables following the Shin et al [29] methodology in the following way:…”
Section: Methodsmentioning
confidence: 99%
“…Adamu et al [13] investigate and find that energy consumption, income, exports variety and Foreign Direct Investment (FDI) positively contribute to the carbon emissions in India. Mahmood et al [10] explore the determinants of CO 2 emissions of Saudi Arabia in the asymmetric settings. They report that the decreasing financial development increases the CO 2 emissions but the decreasing energy consumption helps in reducing CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that countries should consider the effects of their macroeconomic and international trade policies on the environmental side and explore the way it can impact the ecological footprint of the country in the neighbourhood. Mahmood et al (2018) analyzed the pollution in Saudi Arabia. Data from 1971-2014 was analyzed from the Saudi Arabia and both short and long-term relationships were analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%